2007
DOI: 10.1158/0008-5472.can-06-3844
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Xeroderma Pigmentosum C Deficiency and Mutagens on Mutation Rates in the Mouse Germ Line

Abstract: Spontaneous and induced mutation rates at two expanded simple tandem repeat (ESTR) loci were studied in the germ line of xeroderma pigmentosum group C (Xpc) knockout mice defective in global genome nucleotide excision repair. Spontaneous and radiation-induced mutation rates in homozygous Xpc À/À males were significantly higher than those in isogenic wild-type (Xpc +/+ ) and heterozygous (Xpc +/À

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
4
12
1
1
Order By: Relevance
“…We therefore conclude that exposure to the anticancer drugs analyzed here does not affect the size of ESTR mutation changes. These data are in line with the results of our previous studies showing no difference in the structure of spontaneous and radiation-or ethylnitrosourea-induced ESTR mutants in the mouse germ line (37,38). We and others have previously hypothesized that ESTR mutation induction cannot be attributed to the direct targeting of these small genomic loci by ionizing radiation and chemical mutagens (8,9,13,14,39).…”
Section: Resultssupporting
confidence: 92%
“…We therefore conclude that exposure to the anticancer drugs analyzed here does not affect the size of ESTR mutation changes. These data are in line with the results of our previous studies showing no difference in the structure of spontaneous and radiation-or ethylnitrosourea-induced ESTR mutants in the mouse germ line (37,38). We and others have previously hypothesized that ESTR mutation induction cannot be attributed to the direct targeting of these small genomic loci by ionizing radiation and chemical mutagens (8,9,13,14,39).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, in these patients, the cells accumulate mutations in nontranscribed parts of the genome, leading to neoplastic transformation (11). Notably, XPC-knockout mice have heightened predisposition to many types of UV-induced and spontaneous cancers (14,15), indicating that XPC plays a role in the removal of non-UV-related mutations as well. Moreover, lymphocytes from Xpc -/-mice accumulate spontaneous lesions in the hypoxanthine guanine phosphoribosyl transferase (Hprt) gene (16).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in these patients, that have proficient TCR and defective GGR, the cells accumulate mutations, notably UVB-induced photoproducts such as cyclobutane pyrimidine dimers (CPD) and 6-4 photoproducts (6-4pp), in non-transcribed parts of the genome, leading to neoplastic transformation [1]. It has also been shown that XPC knockout mice have heightened predisposition to many types of UV-induced and spontaneous cancers [5, 6], indicating that XPC plays a role in the removal of non-UV-related mutations as well. Moreover, lymphocytes from XPC −/− mice accumulate spontaneous lesions in the hypoxanthine guanine phosphoribosyl transferase (HPRT) gene [7].…”
Section: Introductionmentioning
confidence: 99%